Vascular access in hemodialyis patients - registry data - Stojcheva Taneva, Olivera; Selim, Gjulshen (Lithografia Antoniadis I - Psarras Th G.P., 2014)
The use of arteriovenous fistula over a central venous catheter in hemodialysis patients is recommended whenever possible. It has become the gold standard among all the available permanent vascular accesses for hemodialysis as it is associated with less complications. The aim of our study was to analyze the type of vascular access in hemodialysis patients in our country, FYR of Macedonia and to see its association with other variables recorded by the National Renal Registry in 2009.